PERCEPTIONS OF TEACHERS ON THE PRACTICE TEACHING IN THE IFAD ́S OF DURANGO - Laurencia Barraza Barraza; Juan Francisco Villarreal Gallegos (Ra Ximhai, 2013)
This research reports the preliminary findings found through a survey on teacher practice attended by 38 teachers from Institutes of Teaching Training and Updating (IFAD ́s by their acronym in Spanish) at Durango State. From the answers made by teacher trainer, it is reached to perceive a tension between complacent appreciation about their own practice and the few spaces that have normal schools for collective reflection.